Tubercular prevertebral and epidural abscess presenting as stridor and dysphagia in an infant: A rare presentation of tuberculosis in infancy (Indian Journal of Case Reports, 2016)
Tubercular prevertebral abscess is rare presentation of pott’s spine in infancy. It can lead to life threatening airway obstruction and dysphagia requiring early diagnosis and proper management to prevent consequences. We present a case of 5 month child with tubercular prevertebral and epidural abscess who presented with dysphagia and stridor. Child responded dramatically to anti-tubercular therapy and surgical drainage of abscess. The child is doing well on follow up.